Impact of Phenomenon-Based Learning Model Assisted by Virtual Book-Based Digital Comics on Elementary-School Students' Agile Innovation and Independence in Science Learning - Bachri, B. S.; Tegeh, M.; Jayanta, I. N. L. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2023)
This study aims to analyze the impact of the Phenomenon-based Learning (PhBL) model assisted by virtual book-based digital comics on elementary school students' agile innovation and independence in science learning. This study used a quasi-experimental method with a quasi-experimental with a post-test control group design. The research sample consisted of 58 students, 30 in the experimental group and 28 in the control group. Research data collection used tests and questionnaires. Data analysis was performed using quantitative descriptive analysis methods and inferential statistical analysis. The data analysis technique used was MANOVA, with the results showing a significance value of 0.00, less than 0.05. The study results show that using a phenomenon-based learning (PhBL) model assisted with virtual book-based digital comics positively impacts the development of students' agile innovation and independence, both partially and simultaneously. The mean score of agile innovation and independence in the group taught using the PhBL model assisted with virtual book-based digital comics is higher. Therefore, the phenomenon-based learning (PhBL) model assisted with virtual book-based digital comics can be recommended as one of the innovative learning models to overcome the not-yet-optimal students' agile innovation and independence.